PENGUKURAN KINERJA CUSTOMER RELATIONSHIP MANAGEMENT (CRM) MENGGUNAKAN CRM SCORECARD DAN OMAX - Ahmad Aviv Mahmudi; ngadenan ngadenan (Jurnal Informatika Upgris, 2017)
UMKM Batik Tulis Lasem is one of the superior products from Rembang that continue to be developed by the government. UMKM Batik Tulis Lasem still many difficulties on their progression, especially in marketing, others are the utilization of technology, lack of innovation, capital and low quality of human resources. Another obstacle that is often faced by UMKM who are members of the Koperasi Batik Tulis Lasem are marketing and maintain the existing market. In addition, owners who are members of Koperasi Batik Tulis Lasem also pay less attention to marketing strategy and maintaining customer relationship. Measuring the performance of UMKM Batik Tulis Lasem by identifying KPI (Key Performance Indicator) measure the practice performance of Customer Relationship Management (CRM using CRM Scorecard) through four CRM perspectives. The assessment of each perspective uses the AHP (Analytical Hierarchy Prosses) method and scoring of performance on each level or CRM factors using the OMAX (Objective Matrix) method.Through CRM scorecard describes a performance measurement of the implementation of Customer Relationship Management (CRM) in Koperasi Batik Tulis Lasem so that the results of these measurements show some perspectives that need to be improved efficiency and performance of an organization. From the perspective of performance organizations have two factors, six factors from the perspective of consumer, three factors from the perspective of process, seven factors from the perspective of infrastructure. Four perspective that affect the performance of CRM generally can be known Good Performance of Koperasi Batik Tulis. There are only three criteria that are at the bad level. They are improving participation of management, increase human resources capability and increasing customer relationship value. The results expected to increase customer satisfaction and loyalty in the Koperasi Batik Tulis Lasem . Key word: AHP, Batik Tulis, CRM, CRM scorecard, OMAX.